2008
DOI: 10.1007/s10814-007-9019-6
|View full text |Cite
|
Sign up to set email alerts
|

Siberia at the Last Glacial Maximum: Environment and Archaeology

Abstract: This article focuses on the presence of humans in Siberia and the Russian Far East at the coldest time of the Late Pleistocene, called the Last Glacial Maximum (LGM) and dated to c. 20,000-18,000 rcbp. Reconstruction of the LGM environment of Siberia, based on the latest models and compilations, provides a background for human existence in this region. Most of Siberia and the Russian Far East at c. 20,000-18,000 rcbp was covered by tundra and cool steppe, with some forest formations in the river valleys. Clima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(37 citation statements)
references
References 111 publications
1
36
0
Order By: Relevance
“…These data support Goebel's (1999Goebel's ( , 2002 see also Dolukhanov et al, 2002;Graf, 2005) position that Upper Paleolithic peoples abandoned parts of northern Asia during the LGM and, therefore, do not support Kuzmin's (2008) (Kuzmin and Keates, 2005a,b) assertion that human populations were maintained in all areas of Siberia during this time. With more excavations and dating, however, it could be found that the LGM-gap in the Enisei may be filled.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…These data support Goebel's (1999Goebel's ( , 2002 see also Dolukhanov et al, 2002;Graf, 2005) position that Upper Paleolithic peoples abandoned parts of northern Asia during the LGM and, therefore, do not support Kuzmin's (2008) (Kuzmin and Keates, 2005a,b) assertion that human populations were maintained in all areas of Siberia during this time. With more excavations and dating, however, it could be found that the LGM-gap in the Enisei may be filled.…”
Section: Discussionmentioning
confidence: 85%
“…Recent debate has centered on whether people were capable of inhabiting Siberia during the intervening LGM (Dolukhanov et al, 2002;Goebel, 1999Goebel, , 2002Graf, 2005;Kuzmin, 2008;Kuzmin and Keates, 2005a,b;Vasil'ev et al, 2002). Opinions are linked to acceptance or rejection of 14 C assays dating from 20,000 to 18,000 14 C (24,000-21,500 cal) BP.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A misleading statement is made by Graf when she discusses the LGM issue: ''Upper Paleolithic peoples abandoned parts of northern Asia during the LGM and, therefore, do not support Kuzmin's (2008) (Kuzmin and Keates, 2005) assertion that human populations were maintained in all areas of Siberia [italics are mine -Y.K.] during this time.''…”
mentioning
confidence: 99%